Studies on spray casting of Al-alloys and their composites - Satyanarayana K.G.; Ojha S.N.; Naresh Nath Kumar D.; Sastry G.V.S. (My University, 2025)
A spray nozzle of convergent-divergent configuration was used for spray castings (SC) of A16061/LM25 alloys and their composites. Both monolithic alloys and composites showed equiaxed fine grained microstructure with a variation in grain size from 20 to 30 μm. Some of the regions of the preform also showed cellular solidification structure with globularization of most of the eutectic Si suggesting the effect of rapid solidification. High defect concentration in both SC matrix and their composites was observed with bulk SC samples showing uniformly distributed porosity. TEM studies showed decoration of grain boundaries/presolidified droplets by some precipitates and also vacancy loops. Their aging characteristics indicated lowering of solutionising temperature and aging time to get the same peak hardness as obtained in the alloy produced by ingot metallurgy methods. An ordered phase with unit cell four times larger than Al seems to form during the in situ heating of LM25-SiCp samples while dislocations seem to emerge from the interface between the particle and the matrix. The results are discussed in the light of reported literature on spray casting/melt spinning of Al-alloys and composites. © 2001 Elsevier Science B.V. All rights reserved.